2012
DOI: 10.1016/j.bbamem.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent conformational changes in connexin channels

Abstract: Channels formed by connexins display two distinct types of voltage-dependent gating, termed Vj- or fast-gating and loop- or slow-gating. Recent studies, using metal bridge formation and chemical cross-linking have identified a region within the channel pore that contributes to the formation of the loop-gate permeability barrier. The conformational changes are remarkably large, reducing the channel pore diameter from 15 to 20 Å to less than 4 Å. Surprisingly, the largest conformational change occurs in the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 139 publications
(250 reference statements)
2
80
0
2
Order By: Relevance
“…Two mechanisms have been proposed for voltage gating of gap junction channels; one is through conformational changes of a voltage sensor located in the N-terminus and the second is through the C-terminus acting as a gating particle to block channel pore or stabilize the closed state (35). A recent study has shown that voltage-dependence of the slow gate is located at charged residues of the first-transmembrane region of Cx46 as well as Cx26 and Cx50 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms have been proposed for voltage gating of gap junction channels; one is through conformational changes of a voltage sensor located in the N-terminus and the second is through the C-terminus acting as a gating particle to block channel pore or stabilize the closed state (35). A recent study has shown that voltage-dependence of the slow gate is located at charged residues of the first-transmembrane region of Cx46 as well as Cx26 and Cx50 (36).…”
Section: Discussionmentioning
confidence: 99%
“…In more closely related connexin channels, the pH modulation of Cx47 (20,21) and fast transjunctional voltage (Vj)-dependent gating of Cx40 and Cx43 (22,23) have also been characterized as a ball-and-chain mechanism. In these cases, this type of mechanism was supported by showing that an isolated ball region could rescue inactivation, pH sensitivity, or Vj-dependent gating in truncated channels (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the charge selectivity of a connexin hemichannel is determined by charges dispersed over the permeation pathway (including several charged residues in the NT). (Some of these and related studies are described in more detail in the accompanying article by Bargiello [34]. )…”
Section: Roles Of Nt Amino Acids In Channel Gating Unitary Conducmentioning
confidence: 99%